Transactions en eaux troubles : résurgences de la voix shakespearienne dans Moby-Dick - Ronan Ludot-Vlasak (Revue LISA)
This article explores the way Herman Melville appropriates William Shakespeare’s work in Moby-Dick. Its argument is that by defamiliarising some of Shakespeare’s lines—a corpus that was both alien and familiar to nineteenth-century writers— Melville turns them into his own idiom. This resurgence of the Shakespearean voice is double: although the dramatic element in the novel is often associated with the figure of Ahab, Ishmael also incorporates Shakespearean lines into his narrative. What characterises these (inter)textual transactions is that instead of quoting directly from Shakespeare’s plays, Melville often blurs references in order to appropriate the works of his predecessor. More than the mere imitation of a model, this complex process reveals Shakespeare’s seminal role in Moby-Dick as well as Melville’s poetics of reinvention. Ultimately, it enables the author to explore the dark forces lying beneath the surface of things.